2015
DOI: 10.4141/cjps-2015-119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of sorghum genotypes using GGE biplot

Abstract: Gasura, E., Setimela, P. S. and Souta, C. M. 2015. Evaluation of the performance of sorghum genotypes using GGE biplot. Can. J. Plant Sci. 95: 1205Á1214. In spite of sorghum's drought tolerance, it is largely affected by genotype)environment interaction (GE), making it difficult and expensive to select and recommend new sorghum genotypes for different environments. The objectives of this study were to examine the nature of GE for sorghum grain yield, to identify superior sorghum genotypes for sorghum productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…This is similar to the study which was done by Gasura et al (2015), where they tested 20 sorghum varieties and there was a large effect of GEI about seven times larger than the effect of genotypes. The GGE biplot analysis showed that IPCA1 accounted for 50.72% and IPCA2 accounted for 25.82%, both accounting for a sum of 76.59% (Figure 1) and this showed similarity with study of Gasura et al (2015) where PC1 and 2 explained 36.8 and 29.5%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is similar to the study which was done by Gasura et al (2015), where they tested 20 sorghum varieties and there was a large effect of GEI about seven times larger than the effect of genotypes. The GGE biplot analysis showed that IPCA1 accounted for 50.72% and IPCA2 accounted for 25.82%, both accounting for a sum of 76.59% (Figure 1) and this showed similarity with study of Gasura et al (2015) where PC1 and 2 explained 36.8 and 29.5%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to the study which was done by Gasura et al (2015), where they tested 20 sorghum varieties and there was a large effect of GEI about seven times larger than the effect of genotypes. The GGE biplot analysis showed that IPCA1 accounted for 50.72% and IPCA2 accounted for 25.82%, both accounting for a sum of 76.59% (Figure 1) and this showed similarity with study of Gasura et al (2015) where PC1 and 2 explained 36.8 and 29.5%, respectively. The biplot analysis identified the discriminating ability and representativeness as well as the correlation of environments (Sujay et al, 2014) and genotype average performance and the results showed the importance of testing and comparing genotypes so as to select the ones with specific and wide adaptation accordingly and environments which are representativeness to reduce experimenting costs by discarding unrepresentative locations and those with poor discriminating abilities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, MPOP, BKLN, and CHDS were identified as highly discriminating environments for the QPM hybrids tested in their respective group of environments, so these test environments were considered as “ideal environments” for selecting superior hybrids and for the provision of information that is important for the identification of desirable varieties (Tukamuhabwa et al, 2012). Early‐generation testing in such environments will minimize germplasm development expenses by decreasing the number of varieties to be tested in METs, and inherently minimizing the number of test environments (Gasura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A GGE biplot generated based on the SREG model has proved to be useful in grouping similar environments, identifying ideal testing sites, understanding the correlation of traits with either locations or genotypes and in identifying stable genotypes with high yield (Yan and Kang, 2002;Tinker, 2005, 2006). In Zimbabwe, applications of this technique have been reported in maize (Setimela et al, 2007;Setimela et al, 2010;Kamutando et al, 2013), and recently in sorghum (Gasura et al, 2015), but not yet extended to other crops including cotton. The objective of this study was to determine the importance and magnitude of GE and correlation among cotton traits, and their implications in future cotton breeding and variety recommendation.…”
Section: Introductionmentioning
confidence: 99%